Human Sacrifice, Sentencing and the Death Penalty: Failings of the Supreme Court - Vishwanath, Neetika (Economic and political weekly)
In the judicial discourse on the relationship between human sacrifice and punishment in criminal law, there are glaring errors. Looking closely at the Supreme Court$1 (Bs judgment in Ishwari Lal Yadav v State of Chhattisgarh, the deviation from the principle of individualised sentencing and the consequences of ignoring evidence on the complex anthropological and psychological dimensions of human sacrifice are reflected upon.- Reproduceds
Keywords: Death Penalty; Supreme court - India